The Effect of Islamic OCB, Perceived Organizational Support and Procedural Justice on the Affective Commitments of Millenial Lecturers, with the Mediation of Work Engagement - Nunik Kusnilawati (ITB AAS INDONESIA Surakarta, 2022)
This research is motivated by the existence of a research gap in previous studies and the discovery of phenomena related to the topic of affective commitment. The purpose of this research is to examine and analyze the effect of Islamic OCB, perceived organizational support and procedural justice on work engagement and affective commitment. Then this study examines and analyzes the effect of Islamic OCB, perceived organizational support and procedural justice on affective commitment through work engagement mediation. There are two novelties of research: (1) there is a sub-model of research that places work engagement as a variable that mediates the influence of Islamic OCB on affective commitment. (2) the use of respondents with specific characteristics, namely the millennial generation who work as lecturers with a background in Islamic organizational culture (Islamic privat college). Respondents used as data sources amounted to 197 people, while the population amounted to 428 people. Sample selection by accidental technique. The research instrument used was a questionnaire with 5 levels of response referring to the Likert scale. Data processing and data analysis using SEM-PLS with WarpPLS 7.0 application. In this study used descriptive analysis and inferential analysis. The conclusion of this study is Islamic OCB-organizational support-procedural justice has an effect on work engagement. Likewise, Islamic OCB has an effect on affective commitment. However, organizational support and procedural justice have no effect on affective commitment. The results are different when work engagement is placed as a mediating variable, because the result that emerges is that work engagement mediates the effect of Islamic OCB-organizational support-procedural justice on affective commitment. This research has implications regarding theory of affective commitment, work engagement, Islamic OCB, perceived organizational support, and procedural justice. There are also managerial implications. Keywords: Affective Commitment, Work Engagement, Islamic OCB, Perceived Organizational Support, Procedural Justice.